Overseas Giving: Should Charity Begin at Home? - Tan, Chi Chiu (Institutional Knowledge at Singapore Management University, 2008)
In extending a hand overseas with developmental and humanitarian aid, is Singapore doing what is best for itself and the recipient communities? And what role does its government have to play in this arena? Dr Tan Chi Chiu weighs in.